PARTISIPASI KELOMPOK TANI DALAM PENINGKATAN PRODUKTIVITAS TANAMAN PADI SAWAH DI KECAMATAN PADANGSIDIMPUAN HUTAIMBARU - Lubis, Sistia Ainun; Wilis, Ratna (JURNAL BUANA, 2024)
Padangsidimpuan Hutaimbaru District is the area with the largest rice crop production in Padangsidimpuan City, apart from having a relatively large area of ​​land, this is also influenced by the role of farmer groups in increasing the productivity of lowland rice plants. The objectives of this research are: (1) to describe and discuss the level of participation of farmer groups (2) to describe and discuss the productivity level of lowland rice plants in Padangsidimpuan Hutaimbaru District. This research used a mixed method. The population and sample are members of farmer groups in the District of Padangsidimpuan Hutaimbaru, the sampling technique used is proportional random sampling with the results of 149 members of the farmer groups. Documentation data collection techniques, interviews and questionnaires. Data analysis technique using Sequential Exploratory Design. The results showed that the level of participation of farmer groups was high with a total score of 3,620 or 80.98%. The average productivity level of rice plants in Padangsidimpuan Hutaimbaru District is moderate, namely 5-8 tons/ha, the highest productivity yield is 10.2 tons/ha, and the lowest productivity yield is 4.2 tons/ha.